Technology Challenges In Indonesia Oil And Gas Development - Maizar Rahman; Suprajitno Munadi; Bambang Widarsono; Yusep K Caryana (Testing Center for Oil and Gas LEMIGAS, 2011)
This paper presents the challenges in oil and gas development in Indonesia, especially in technical aspects. In upstream, this country faces the fact that the production as well as the proven reserves of oil is continuing to decline. The challenges are therefore on how to find new resources, how to develop frontier area and how to produce more oil from the remaining oil in place in the existing fields. The oil deposit and traps are small, but also complexes. Very limited primary data makes it difficult to have a discovery. More accurate, intensive and comprehensive exploration data are therefore needed which, in turn, will need the use of the most sophisticated exploration technology. On the other hand it isrecommend that Government of Indonesia should generate primary exploration data prior to oil and gas prospecting. Regarding production, there is still hope to maintain the production level by exploiting further the remaining oil in place, the effort of which will need the use of advanced technology. The future of EOR application in Indonesia is bright and steps have been taken towards the objective. However, some important technical matters should still be overcome. In petroleum refining Indonesia faces increasing demand, the need of lighter products, more stringent fuels specifications, demand increase of petrochemical products, old and low complexity existing refineries and not sufficient margin for developing new refinery. The development of new refineries seems a must from the view of energy security. However, low margin should be overcome by appropriate strategy such as integration with petrochemical and employing more efficient technology. Some challenges that need to be considered in gas development in Indonesia include increasing gas demand,more gas reserve offshore, scattered gas consumers, limited infrastructure, not optimal domestic utilization and weak willingness to pay. Several technological approaches should be done to overcome those challenges.